2017
DOI: 10.1253/circj.cj-16-1130
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Obesity on the Prognostic Impact of Atrial Fibrillation in Heart Failure With Preserved Ejection Fraction

Abstract: Background: Although obesity is associated with left ventricular hypertrophy, diastolic dysfunction, and occurrence of atrial fibrillation (AF), obese heart failure (HF) patients have a more favorable clinical outcome (obesity paradox). The clinical impact of AF on obese or lean HF patients has not been fully elucidated. Methods and Results:We analyzed 1,681 patients who were enrolled in the West Tokyo Heart Failure Registry (WET-HF Registry), a multicenter, prospective cohort registry from 2005 through 2014. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 47 publications
1
6
2
Order By: Relevance
“…In the Japanese HF population, the proportion of overweight patients (BMI ≥ 25 kg/m 2 ) was reported to be 27%. 20 In the present study, however, the proportion of overweight or obese patients was only 16%. This difference in the proportion of overweight or obese patients was probably because the patients who participated in our study were more elderly.…”
Section: Discussioncontrasting
confidence: 71%
“…In the Japanese HF population, the proportion of overweight patients (BMI ≥ 25 kg/m 2 ) was reported to be 27%. 20 In the present study, however, the proportion of overweight or obese patients was only 16%. This difference in the proportion of overweight or obese patients was probably because the patients who participated in our study were more elderly.…”
Section: Discussioncontrasting
confidence: 71%
“…However, studies show that obese heart failure patients with AF have a significantly lower risk of all-cause mortality and rehospitalization for worsening heart failure compared to normal weight patients. 29 In our study, AF was an independent predictor of log NT-proBNP. In patients with heart failure and AF, BNP is mainly produced in the atrium, although there are fewer myocardial cells.…”
Section: Dovepresssupporting
confidence: 50%
“…Significant correlations were found between NT-pro BNP and parameters such as mitral regurgitation velocity, aortic regurgitation end-diastolic velocity, The prevalence of AF in patients with HF is less than 10% in the NYHA class 1 HF patients, while it increases up to 50% as the NYHA functional capacity worsens [17]. Multi-center studies [18,19] of HF with preserved EF reported an increased incidence of AF. In this study, in which the NYHA functional capacity was 3 (2-4), we detected PAF in approximately half of the patients.…”
Section: Discussionmentioning
confidence: 95%